Protective Efficacy of Rhomboid-Like Protein 3 as a Candidate Antigen Against Eimeria maxima in Chickens - Chen, Chen; Tian, Di; Su, Junzhi; Liu, Xiaoqian; Shah, Muhammad Ali A.; Li, Xiangrui; Xu, Lixin; Yan, Ruofeng; Song, Xiaokai (Frontiers in Microbiology, 2021)
Avian coccidiosis brings tremendous economic loss to poultry industry worldwide. The third generation vaccine including subunit and DNA vaccines exhibited promising developmental prospects. In previous study, we found rhomboid-like protein 3 of Eimeria maxima (EmROM3) was involved in the invasion by the parasite. However, the protective efficacy of EmROM3 against Eimeria maxima (E. maxima) remains unknown. In this study, EmROM3 gene was cloned and ligated with expression vectors to produce recombinant protein of EmROM3 (rEmROM3) and eukaryotic expression plasmid of pVAX1-EmROM3 respectively. Chickens were intramuscularly immunized with rEmROM3 and pVAX1-EmROM3 to determine the EmROM3-induced immune response. Serum IgG antibody level of the immunized chickens was determined with indirect ELISA (enzyme-linked immunosorbent) to determine the induced humoral immune response. Transcript level of splenic cytokines and proportion of T cell subsets were detected by quantitative real-time PCR (qPCR) and flow cytometry assay respectively to determine the induced cellular immune response. Finally, protective efficacy of rEmROM3 and pVAX1-EmROM3 against challenge with E. maxima was evaluated by immunization-challenge trials. The results revealed that the purified rEmROM3 reacted with chicken anti-E. maxima serum. Recombinant plasmid of pVAX1-EmROM3 was transcribed and translated in injected muscle from the vaccinated chickens. In the rEmROM3 vaccinated group and pVAX1-EmROM3 vaccinated group, the IgG titers, proportions of CD4+ and CD8+ T cells, and transcript level of splenic cytokines were significantly increased compared with the control groups. The immunization-challenge trial revealed that immunization with rEmROM3 and pVAX1-EmROM3 leaded to restored weight gain, alleviated enteric lesion, decreased oocyst output as well as higher anti-coccidial index (ACI) compared with control groups, indicating partial protection against challenge by E. maxima. These results indicate that EmROM3 is an effective candidate antigen for developing subunit or DNA vaccines against infection by E. maxima.